2002
DOI: 10.1097/00001813-200206000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics of non-break weekly paclitaxel (Taxol) and pharmacokinetics of Cremophor-EL vehicle: results of a dose-escalation study

Abstract: We characterized the toxicity and determined the maximum tolerated dose of non-break weekly paclitaxel (Taxol) in chemotherapy-naive cancer patients, and studied pharmacokinetics of the formulation vehicle Cremophor-EL with this schedule. Twenty-three patients with primary refractory solid tumors received weekly paclitaxel at the dose range of 70-200 mg/m2. As dose-limiting toxicity we defined granulocytopenia grade > or =2 causing a treatment delay for more than 2 weeks, or febrile neutropenia or grade >2 org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…However, high doses and prolonged infusion can markedly increase the terminal half-life. 9 Cremophor EL itself is considered a neurotoxic agent and, therefore, could cause a delayed seizure disorder. It has been associated with clonic seizures and burst-suppression patterns, as seen on electroencephalograms in rats.…”
Section: Discussionmentioning
confidence: 99%
“…However, high doses and prolonged infusion can markedly increase the terminal half-life. 9 Cremophor EL itself is considered a neurotoxic agent and, therefore, could cause a delayed seizure disorder. It has been associated with clonic seizures and burst-suppression patterns, as seen on electroencephalograms in rats.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the toxicity of dose-dense taxane seemed to be well tolerated because of absence of relevant toxicity [94]. A pharmacokinetic study revealed that paclitaxel can be administered weekly at doses of 110 mg/m 2 without interruption, while neutropenia precluded scheduled administration of doses ≥ 130 mg/m 2 [94,117]. In theory, weekly dose-dense paclitaxel provided the better cytotoxicity to tumors, through more sustained exposure, limiting the emergence of tumors resistant to chemotherapy, enhancing the apoptotic and antiangiogenic effect, and improving the therapeutic index [94,[118][119][120], although the single use of dose-dense paclitaxel for the first-line chemotherapy treatment of patients with ETOC seemed to be not approved by clinical trials [109,110].…”
Section: Rationale Of Dose-dense Therapymentioning
confidence: 99%
“…This neuropathy is characterized by intense pain in the extremities, tingling, numbness (paraesthesia), a paradoxical burning pain in response to cold temperatures, and loss of proprioception (Briasoulis et al, 2002, Dina et al, 2001, Dougherty et al, 2004, Forsyth et al, 1997, Lipton et al, 1989, Wiernik et al, 1987). Neurophysiologic examination of patients with paclitaxel-induced peripheral neuropathy reveals a decrease in sensory nerve conduction velocity and compound action potential amplitude (Augusto et al, 2008, Dougherty et al, 2004, Sahenk et al, 1994).…”
Section: Introductionmentioning
confidence: 99%